Comprehensive Preventive and Therapeutic Oral Health Care: A Case Report of Mucopolysaccharidosis Type IV A in a Pediatric Patient - HP, Chanchala; Harjai, Gunica; Doddawad, Vidya G.; S, Manjual (Puerto Rico Health Sciences Journal, 2023)
Mucopolysaccharidosis (MPS) is a metabolic disorder resulting from a deficiency of lysosomal enzymes. It is an autosomal recessive disorder with similar incidences in men and women. Mucopolysaccharidosis type IV A is caused by a deficiency of N-acetylgalactosamine-6-sulfatase, which deficiency is, in turn, caused by alterations in the GALNS gene. It is marked by a short stature, a pigeon chest, frontal bossing, kyphosis, and a flat nasal bridge. Intraorally, macroglossia, hypodontia, dentinogenesis imperfecta, a broad mouth, and an anterior open bite are some of the common features. The present paper reports on a case of MPS in a 5-year-old male patient, along with providing a review of the literature and insight into the oral manifestations related to MPS IV A, also called Morquio A syndrome, and its dental treatment. It aims to highlight the clinical recommendations for oral health care in such cases during different phases of MPS IV A treatment.